Pengaruh Komposisi dan Seleksi Pakan terhadap Performans Rusa Jawa (Cervus timorensis) di Stasiun Flora Fauna Bunder, Kabupaten Gunungkidul. - Subeno (Subeno) (Buletin Peternakan, 2008)
The objectives of this research are to determine food composition preferred feeds and performance of Java deer. Survey of research was conducted from August to September 2007. Data collected by selecting the group of java deer, then monitoring was done on the compositionof offered feed.